Numerical assessment on the hydrothermal behavior and irreversibility of MgO-Ag/water hybrid nanofluid flow through a sinusoidal hairpin heat-exchanger. (June 2020) - Li, Zhixiong; Shahsavar, Amin; Niazi, Kavian; Al-Rashed, Abdullah A.A.A.; Rostami, Sara
Abstract: The aim of this work is to study the hydrothermal and irreversibility characteristics in forced convection flow of Ag-MgO/water hybrid nanofluid through a sinusoidal hairpin heat-exchanger, numerically. The impact of nano-additive concentration ( φ ), Reynolds number ( Re ) and amplitude of the sinusoidal tube are investigated on the heat-exchanger performance form both the first law and second law points of view. The considered performance matrices are heat transfer rate, total heat transfer coefficient, heat-exchanger effectiveness, pressure loss, pumping power as well as the irreversibilities due to flow friction and heat transfer. The findings indicated that boosting the Re and φ causes an enhancement in the heat transfer, while the reverse is true about the remaining performance aspects. In addition, it was found that the irreversibility due to flow friction intensifies by boosting either Re or φ . Moreover, the outcomes revealed that the heat transfer is the main source of irreversibility in the flow of hybrid nanofluid (NF) inside a sinusoidal hairpin heat-exchanger. Furthermore, it was reported boosting the amplitude results in a decrease in the performance index of the heat-exchanger.